2019
DOI: 10.1016/j.toxrep.2019.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity assessment of the green Dunaliella salina microalgae

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 19 publications
(20 reference statements)
1
11
0
Order By: Relevance
“…These results are in line with a previous study that showed that pretreatment with D. salina microalga (1000 mg/kg) normalized liver enzyme levels in rats intoxicated with paracetamol [40]. D. salina has also been shown to be safe [41] and exert a hepatoprotective action in carbon tetrachloride-induced liver toxicity via the presence of many forms of carotene and xanthophylls [42].…”
Section: Discussionsupporting
confidence: 90%
“…These results are in line with a previous study that showed that pretreatment with D. salina microalga (1000 mg/kg) normalized liver enzyme levels in rats intoxicated with paracetamol [40]. D. salina has also been shown to be safe [41] and exert a hepatoprotective action in carbon tetrachloride-induced liver toxicity via the presence of many forms of carotene and xanthophylls [42].…”
Section: Discussionsupporting
confidence: 90%
“…The third and fourth groups were administered D. salina (100 and 200 mg/kg; p.o. ), respectively [26,27], after TAA injection for 7 days.…”
Section: Methodsmentioning
confidence: 99%
“…[18] for 30 days. Groups 4 and 5: diabetic rats received D. salina powder (100 & 200 mg/kg) [19,20] for 30 days.…”
Section: Methodsmentioning
confidence: 99%